Conjunctival biomicroscopy in the diagnosis of microcirculatory disorders in systemic sclerosis: A new look at the “old” method - N. V. Korneeva; E. N. Otteva; K. V. Zhmerenetsky; M. A. Kovaleva; T. S. Panevin (Научно-практическая ревматология)
Microcirculatory (MC) disorders in systemic sclerosis (SS) are an important part of pathogenesis, morphogenesis, determine the clinical picture of the disease, the severity of the patient’s condition and prognosis. The authors draw attention to a direct method for studying microcirculatory disorders – conjunctival biomicroscopy (CBM). The use of improved equipment for conducting CBM and the survey algorithm allows at the present stage to improve the quality of the data obtained, to simplify and standardize the CBM procedure, to record and analyze new MC predictors.The study of the correlations between MC changes identified in CBM in patients with SS, with the data of the clinical picture, will make it possible to determine a limited set of the most significant MC parameters, simplify the analysis of primary CBM data and take a fresh look at the CBM method, rethinking its diagnostic capabilities SS, which determined the aim of this study.Materials and methods. In 48 patients suffering from SS (mean age 51±1.7 years), MC was studied by the direct method – conjunctival biomicroscopy. Quantitative parameters of MC are compared with the clinical manifestations of SS by the methods of linear Pearson correlation and Spearman non-linear correlation. The critical value of the level of statistical significance in testing null hypotheses was taken to be 0.05.Results. The main clinical manifestations of SS: the duration of the disease (months), skin count (points), the activity of the disease (points), the duration of skin syndrome (months) and the duration of vascular syndrome (months) showed statistically significant linear and non-linear correlation with seven MC parameters: the value of the arteriolo- to-venule ratio (AVR), five parameters characterizing the density of capillaries on the bulbar conjunctiva and the average diameter of capillaries.Conclusion. A limited set of the most informative MC signs in the form of AVR and the number of capillaries in various areas of the temporal section of the bulbar conjunctiva greatly simplify the interpretation of CBM data and allow a new look at the diagnostic capabilities of the “old” method in SS. A promising direction, in our opinion, is the further study of the indicated MC parameters and the identification of possible correlations with the data of laboratory, instrumental methods of research and assessment of the dynamics of the indicated MC parameters in case of SS.